Factors influencing females’ work in the construction companies - Ahmed Mohammed Kamaruddeen; Khairin Norhashidah Khalid; Wahida Wahi (Penerbit Universiti Kebangsaan Malaysia, 2019)
Literature has shown that the percentage of females working in the construction industry is less compared to the males. For this reason, issues relating to gender in construction industry have attracted the attention of scholars in recent time. This paper aims to identify the factors influencing females’ work in the construction companies operating in Kedah State, Malaysia. Using simple random sampling technique, copies of a structured questionnaire were distributed to 30 female construction workers. The collected data were analyzed using Statistical Package for Social Science (SPSS) version 20. It was found that both internal and external factors have significant relationship with females’ choice of career in the construction company. The factors identified in this study can be useful to the policy makers regarding employment of females in Malaysia.